Hatching Egg Sanitizers Based on Essential Oils: Microbiological Parameters, Hatchability, and Poultry Health - Gabriel da Silva Oliveira; Concepta McManus; Pedro Henrique Gomes de Sá Santos; Davi Emanuel Ribeiro de Sousa; José Luiz de Paula Rôlo Jivago; Márcio Botelho de Castro; Vinícius Machado dos Santos (MDPI AG, 2024)
Background: Eggshell contamination threatens the viability of hatching eggs. This contamination can be caused by harmless, opportunistic, or pathogenic bacteria. Although necessary, the use of synthetic antibiotics to treat eggshells can present several significant problems: They can be toxic and damage the shell, and, most worryingly, they can lead to bacterial resistance. Faced with these challenges, the objective of this research was to create and test a sanitizing plan for hatching eggs using essential oils derived from Citrus aurantifolia (CAEO), Ocimum basilicum (OBEO), or Allium sativum (ASEO). Methods: Sanitizing solutions containing specific concentrations of these essential oils were prepared, and their antimicrobial properties and contributions to poultry safety and hatching parameters were investigated. Results: The bacterial load was reduced in eggshells sanitized with essential oils, and the degree of bacterial inhibition, along with their safety profile, may be directly related to optimal hatchability rates, lower incidences of contaminated dead embryos, and the hatching of healthy chicks. Conclusions: Together, these results reinforce the importance of essential oils in the development of effective and safe treatments for managing hatching eggs.